IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI UNTUK MENGOPTIMALISASI HASIL BELAJAR IPAS PESERTA DIDIK KELAS IV SD INPRES LABAT KOTA KUPANG - Kristina E. Noya Nahak (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
Each student possesses diverse characteristics, abilities, and needs. However, this is often overlooked by educators and contemporary parents. Teachers have a limited understanding of how a student's academic achievement must be comprehensively viewed within the context of social, emotional, physical, and psychological development. The aim of this research is to provide an overview of the implementation of differentiated learning to optimize the learning outcomes of fourth-grade students at SD Inpres Labat, Kota Kupang, specifically in the subject of IPAS (Integrated Science). The research methodology employed is descriptive analytics with a qualitative approach. Data analysis is conducted through triangulation, combining observation results, interviews, and documentation to verify data.The research results indicate that the implementation of differentiated learning in the IPAS subject has a positive impact on both students and teachers. Learning outcomes improve, and students feel comfortable in their learning environment. Each student develops according to their abilities and skills. Teachers no longer compare the abilities and skills of each student but are more motivated to create more active and creative learning experiences using diverse teaching strategies. Learning begins with cognitive and non-cognitive assessments to determine students' interests, learning styles, and backgrounds. Differentiation strategies in content, process, and product are implemented by teachers according to students' learning needs. One of the challenges in implementing differentiated learning is time. Teachers require more time than the allocated class hours because they need to group students and organize lessons according to the needs of the learners.